Industrial training report: FIC Kuching Sdn Bhd / Nur Aliah Aida Zullkafli - Zullkafli, Nur Aliah Aida (Universiti Teknologi MARA, Perlis, 2024)
My internship was conducted at FIC Kuching Property Sdn Bhd, situated in Felda Residence Hot Spring, Sungkai Perak. The internship spanned a duration of 24 weeks, beginning on March 1, 2024, and concluding on August 9, 2024. During this period, I was assigned to the Human Resources Department under the guidance of Mrs. Nor Ashikin Binti Amir Hamzah. Throughout my internship, my responsibilities centered on managing tasks related to Human Resources, Finance and Front Office . I collaborated closely with team members, actively participating in various programs and events. Overall, my internship was rich with opportunities for learning and gaining experience in the field of Human Resources, while also acquiring valuable insights into finance management and event coordination. Working within the hotel industry provided me with ample networking opportunities and invaluable experience for my future career endeavors.